Porous cerium fluoride catalyst as well as preparation method and application thereof

By using porous cerium fluoride catalyst in fuel cells, the high cost, permeability and stability of the anode catalyst are solved, and high activity and stability are achieved, which is suitable for large-scale applications.

CN119812373AActive Publication Date: 2025-04-11INNER MONGOLIA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411949082.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In existing fuel cells, there are high costs, methanol permeability problems, and insufficient stability and durability, and it is necessary to develop high-activity and high-stability catalysts.

Method used

The composite oxide precursor was synthesized by impregnation method, and the porous cerium fluoride catalyst was prepared by hydrofluoric acid etching. Silica was used as a template to form a porous structure, increasing the specific surface area and active sites of the catalyst.

Benefits of technology

It improves the activity and stability of the catalyst, enhances the proton transfer speed, reduces the amount of precious metals, and is also suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812373A_ABST
    Figure CN119812373A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fuel cells, and discloses a porous cerium fluoride catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: synthesizing a composite oxide precursor by taking silicon dioxide as a template and adopting an impregnation method, roasting to obtain a composite oxide, etching and fluorinating by adopting hydrofluoric acid to prepare cerium fluoride, and finally mixing the porous cerium fluoride, a carrier, a platinum source aqueous solution and an alcohol solution for hydrothermal reaction to obtain the porous cerium fluoride catalyst. The template skeleton is etched by hydrofluoric acid to form a porous structure, the pore diameter of the cerium fluoride carrier is controlled by adjusting the concentration of hydrofluoric acid, the specific surface area of the catalyst carrier is increased, more active sites are provided for adsorption of platinum nanoparticles, the proton transmission speed can be increased, the consumption of precious metal is reduced, and meanwhile, the specific surface area of the catalyst carrier is increased. The activity of the catalyst is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a porous cerium fluoride catalyst and a preparation method and application thereof. Background Art

[0002] Population growth and the increasing importance of science and technology have led to a surge in energy demand.

[0003] Currently, electricity sources mainly come from fossil fuels, which has a negative impact on the environment, and the number of technology users that rely on electricity continues to increase. It is reported that nearly 6.2 billion tons of carbon dioxide were released into the atmosphere in 2000, of which about 40% was due to emissions from electricity production. Therefore, researchers are encouraged to find renewable and eco-friendly alternative energy sources. Recently, advances in the field of direct alcohol fuel cells (DAFCs) have become a trend for researchers and manufacturers to find alternative fuels for generating electrical energy. The benefits of using alcohol fuel cell technology: bio-friendliness, low cost, portability, and high energy density of alcohols (such as methanol and ethanol). For example, direct methanol fuel cells (DMFCs) do not require charging, have low temperature operability, have a long service life, and are used in systems that can be refueled quickly. However, DMFCs still have challenges that need to be solved. Problems encountered in DMFCs include high cost, methanol permeation problems through proton exchange membranes, and problems in maintaining long-term stability and durability during operation. Therefore, solving the above problems and developing highly active and highly stable anode catalysts are of great significance to the widespread application of DMFCs.

[0004] Ceria has received considerable attention as a catalyst support, mainly because of its oxygen vacancies and variable valence (Ce 4 + / Ce 3+ ). Therefore, cerium oxide can provide abundant OH by storing and releasing oxygen. ads , effectively eliminating poisoning intermediates such as CO. However, pure ceria has poor thermal stability at high temperatures and can sinter, resulting in the loss of its key oxygen storage capacity and redox properties. Fluorination of cerium oxide can make it porous and increase catalytic activity. At the same time, cerium fluoride (CeF3) as a composite component has a reversible Ce 3+ and Ce 4+Valence phase transition has been used to optimize the surface electronic state. CeF3 has three fluorine atoms with strong electronegativity (electronegativity is about 4.0), which can act as a perfect electron acceptor, thereby further adjusting the electron distribution of the loaded precious metal. Currently, the commonly used fluorination methods include heating and decomposing fluorides for fluorination and acid fluorination. However, due to the uneven heating process of fluorides, the concentration of hydrogen fluoride gas produced does not reach the purity required for fluorination, and the reaction with cerium oxide is incomplete. Only a partial reaction occurs on the surface, so the prepared cerium fluoride has insufficient crystallinity and insufficient specific surface area. Therefore, how to optimize the preparation process of cerium fluoride is an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present invention is to provide a porous cerium fluoride catalyst and a preparation method and application thereof, so as to solve the above-mentioned problems existing in the anode catalyst of the existing fuel cell.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a porous cerium fluoride catalyst, comprising the following steps:

[0008] Mixing cerium salt, dicyandiamide, silicon dioxide and water, and then heating to evaporate the water to obtain a composite precursor; calcining the composite precursor to obtain a composite oxide;

[0009] The composite oxide is etched in hydrofluoric acid to obtain porous cerium fluoride;

[0010] The porous cerium fluoride, a carrier, a platinum source aqueous solution and an alcohol solution are mixed, and then a hydrothermal reaction is carried out to obtain a porous cerium fluoride catalyst.

[0011] Preferably, in the above-mentioned method for preparing a porous cerium fluoride catalyst, the mass ratio of the cerium salt, dicyandiamide and silicon dioxide is 1-10:1-5:1-10.

[0012] Preferably, in the above-mentioned method for preparing a porous cerium fluoride catalyst, the process of mixing the cerium salt, dicyandiamide, silicon dioxide and water also includes stirring; the stirring time is 12 to 72 hours; and the stirring speed is 300 to 1600 rpm.

[0013] Preferably, in the above method for preparing a porous cerium fluoride catalyst, the calcination temperature is 360 to 750° C.; and the calcination time is 4 to 12 hours.

[0014] Preferably, in the above-mentioned method for preparing a porous cerium fluoride catalyst, the concentration of the hydrofluoric acid is 1 to 10 mol / L; the etching temperature is 10 to 40° C.; and the etching time is 1 to 3 hours.

[0015] Preferably, in the above-mentioned method for preparing a porous cerium fluoride catalyst, the usage ratio of the porous cerium fluoride, the carrier, the platinum source aqueous solution and the alcohol solution is 1-100g: 10-100g: 1-30L: 1-100L.

[0016] Preferably, in the above-mentioned method for preparing a porous cerium fluoride catalyst, the concentration of the platinum source aqueous solution is 0.01-0.2 mol / L; the platinum source in the platinum source aqueous solution is one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, and platinum acetylacetonate.

[0017] Preferably, in the above-mentioned method for preparing a porous cerium fluoride catalyst, the temperature of the hydrothermal reaction is 120-150° C.; and the time of the hydrothermal reaction is 1-4 hours.

[0018] The invention also provides a porous cerium fluoride catalyst prepared by a method for preparing the porous cerium fluoride catalyst.

[0019] The invention also provides an application of a porous cerium fluoride catalyst in a fuel cell.

[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention adopts an impregnation method to synthesize a composite oxide precursor, and then adopts hydrofluoric acid etching and fluorination to prepare cerium fluoride. The advantage is that the concentration of hydrofluoric acid is easy to control, and the pore size of the cerium fluoride carrier can be controlled by adjusting the concentration of hydrofluoric acid, so that it can be applied to different catalytic environment fields. At the same time, the present invention uses silicon dioxide as a template, then coats the surface with cerium dioxide, and finally uses hydrofluoric acid to etch away the template skeleton to form a porous structure, which increases the specific surface area of ​​the catalyst carrier, provides more active sites for the adsorption of precious metal nanoparticles such as platinum, can accelerate the proton transmission speed, and while reducing the amount of precious metals, also improves the catalyst activity.

[0022] (2) The catalyst preparation method of the present invention is simple, has low process requirements, and is suitable for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for describing the embodiments or the prior art are briefly introduced below.

[0024] Figure 1 X-ray diffraction patterns of the catalysts prepared in Example 1 and Comparative Example 1;

[0025] Figure 2Transmission electron microscope images and EDS spectra of the porous cerium fluoride prepared in Example 1; wherein a) is a TEM bright field image, b) is a TEM dark field image, c) is a high-resolution TEM image, d) is an enlarged TEM image with a scale of 200 nm, e) is a high-angle annular dark field image, f) is an EDS spectrum of Ce, g) is an EDS spectrum of F, h) is an EDS spectrum of O, and i) is an EDS spectrum of Si;

[0026] Figure 3 The ECSA diagrams of the catalysts prepared in Example 1 and Comparative Example 1;

[0027] Figure 4 Impedance diagrams of the catalysts prepared in Example 1 and Comparative Example 1;

[0028] Figure 5 This is a stability test chart of the catalysts prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing a porous cerium fluoride catalyst, comprising the following steps:

[0030] Mixing cerium salt, dicyandiamide, silicon dioxide and water, and then heating to evaporate the water to obtain a composite precursor; calcining the composite precursor to obtain a composite oxide;

[0031] The composite oxide is etched in hydrofluoric acid to obtain porous cerium fluoride;

[0032] The porous cerium fluoride, a carrier, a platinum source aqueous solution and an alcohol solution are mixed, and then a hydrothermal reaction is carried out to obtain a porous cerium fluoride catalyst.

[0033] In the present invention, the cerium salt is preferably cerium nitrate.

[0034] In the present invention, the mass ratio of the cerium salt, dicyandiamide and silicon dioxide is preferably 1-10:1-5:1-10, more preferably 1-5:1-2:1-4, and more preferably 1:1.1:2.

[0035] In the present invention, the usage ratio of the silicon dioxide to water is preferably 1-10 g:1-100 mL, more preferably 1-3 g:10-50 mL, and even more preferably 1 g:12.5 mL.

[0036] In the present invention, the process of mixing the cerium salt, dicyandiamide, silicon dioxide and water also includes stirring; the stirring time is preferably 12 to 72 hours, more preferably 14 to 24 hours, and more preferably 15 hours; the stirring speed is preferably 300 to 1600 rpm, more preferably 800 to 1600 rpm, and more preferably 1600 rpm.

[0037] In the present invention, the heating temperature is preferably 90-150° C., more preferably 100-140° C., and more preferably 120° C.; the heating time is preferably 2-5 h, more preferably 4-5 h, and more preferably 5 h.

[0038] In the present invention, the calcination temperature is preferably 360-750°C, more preferably 650-750°C, and more preferably 750°C; the calcination time is preferably 4-12h, more preferably 5-10h, and more preferably 6h.

[0039] In the present invention, the concentration of the hydrofluoric acid is preferably 1-10 mol / L, more preferably 2-5 mol / L, and more preferably 2 mol / L; the etching temperature is preferably 10-40°C, more preferably 20-30°C, and more preferably 25°C; the etching time is preferably 1-3h, more preferably 2-3h, and more preferably 3h.

[0040] In the present invention, the usage ratio of the composite oxide to hydrofluoric acid is preferably 1-100 g:1-100 L, more preferably 10-60 g:10-30 L, and even more preferably 50 g:20 L.

[0041] In the present invention, the etching process also includes stirring; the stirring speed is preferably 400 rpm.

[0042] In the present invention, the carrier is preferably one of a carbon source, a metal carbide, a nitride, a chloride or a hydroxide, more preferably a carbon source or a metal carbide, and more preferably graphene.

[0043] In the present invention, the alcohol solution is preferably ethylene glycol, methanol or ethanol, more preferably ethylene glycol or methanol, and more preferably ethylene glycol.

[0044] In the present invention, the usage ratio of the porous cerium fluoride, the carrier, the platinum source aqueous solution and the alcohol solution is preferably 1-100g:10-100g:1-30L:1-100L, more preferably 50-100g:60-100g:5-20L:40-70L, and more preferably 100g:100g:10L:50L.

[0045] In the present invention, the concentration of the platinum source aqueous solution is preferably 0.01-0.2 mol / L, more preferably 0.03-0.1 mol / L, and more preferably 0.05 mol / L; the platinum source in the platinum source aqueous solution is preferably one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, and acetylacetonatoplatinum, more preferably one of chloroplatinic acid, potassium chloroplatinate, and sodium chloroplatinate, and more preferably chloroplatinic acid.

[0046] In the present invention, the method for mixing the porous cerium fluoride, the carrier, the platinum source aqueous solution and the alcohol solution is preferably to ultrasonicate first and then stir; the frequency of the ultrasound is preferably 15 to 50 KHz, more preferably 20 to 40 KHz, and more preferably 30 KHz; the time of the ultrasound is preferably 10 to 100 min, more preferably 60 to 90 min, and more preferably 80 min; the stirring speed is preferably 800 rpm; the stirring time is preferably 1 to 5 h, more preferably 2 to 4 h, and more preferably 3 h.

[0047] In the present invention, the temperature of the hydrothermal reaction is preferably 120-150°C, more preferably 125-140°C, and more preferably 130°C; the time of the hydrothermal reaction is preferably 1-4h, more preferably 2-4h, and more preferably 2h.

[0048] In the present invention, after the hydrothermal reaction is completed, filtration and vacuum drying are also included; the filtration pressure is preferably 0.05-0.09 MPa, more preferably 0.06-0.09 MPa, and more preferably 0.09 MPa; the filtration time is preferably 1-8 h, more preferably 2-5 h, and more preferably 3 h; the vacuum drying temperature is preferably 40-80 ° C, more preferably 50-70 ° C, and more preferably 60 ° C; the vacuum drying time is preferably 2-8 h, more preferably 3-6 h, and more preferably 4 h.

[0049] The invention also provides a porous cerium fluoride catalyst prepared by a method for preparing the porous cerium fluoride catalyst.

[0050] The invention also provides an application of a porous cerium fluoride catalyst in a fuel cell.

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Example 1

[0053] This embodiment provides a porous cerium fluoride catalyst, and the preparation method thereof comprises the following steps:

[0054] 53.97 g of cerium nitrate, 60 g of dicyandiamide, and 120 g of silicon dioxide were weighed and dissolved in 1.5 L of water, stirred and mixed at a stirring rate of 800 rpm for 18 h to form a yellow solution, heated and evaporated at 120 ° C for 4 h, and then calcined at 750 ° C in a muffle furnace for 6 h to obtain a composite oxide; 50 g of the composite oxide was etched in 10 L 2 mol / L hydrofluoric acid solution at a stirring rate of 400 rpm at 26 ° C for 3 h, and then filtered, washed, and dried to obtain porous cerium fluoride; 5 g of Porous cerium fluoride, 10L of 0.05mol / L chloroplatinic acid solution, 100g of graphene, and 50L of ethylene glycol solution were mixed, ultrasonicated at 30KHz for 80min, stirred at 800rpm for 3h, and then placed in a reactor for hydrothermal reaction at 130℃ for 2h to obtain a black turbid liquid, which was vacuum filtered at a pump pressure of 0.09MPa for 3h, and then vacuum dried at 60℃ for 4h to obtain a porous cerium fluoride catalyst, recorded as Pt-CeO2-KS / RGO.

[0055] The electrochemical performance of the catalyst prepared in this example was tested. After adding the catalyst, the peak current density of electrocatalytic methanol could reach 1500 A / g. Pt .

[0056] Comparative Example 1

[0057] This comparative example provides a cerium oxide catalyst, which is specifically referred to Example 1, except that the composite oxide is not etched with a hydrofluoric acid solution, and the cerium oxide catalyst finally obtained is recorded as Pt-CeO2 / RGO.

[0058] The catalysts prepared in Example 1 and Comparative Example 1 were subjected to X-ray diffraction analysis. The results are as follows: Figure 1 As shown. Figure 1 It can be seen from the figure that the Pt in the catalyst of Example 1 has a face-centered cubic structure, and in addition to the peak of Pt, there is also an obvious peak of cerium fluoride. Figure 1 It can also be seen that the crystallinity of the cerium fluoride-supported catalyst after etching is higher than that of pure cerium oxide.

[0059] The porous cerium fluoride prepared in Example 1 was observed under a transmission electron microscope. Figure 2 As shown. Figure 2It can be seen that the morphology of the obtained materials mainly includes nanorods and nanospheres, and the nanospheres are uniformly wrapped on the nanorods. The energy spectrum analysis results show that the obtained materials are all cerium fluoride, with a smooth surface and a hollow transparent structure of the nanorods. This is due to the HF etching and the rapid reconstruction of metal fluorides to form a hollow nanorod structure with a large number of particles, thereby increasing the electrochemical surface area and exposing more active sites. The EDS surface scan results show that the F element and the Ce element are evenly distributed on the nanorod and nanosphere particles, proving that hydrofluoric acid successfully etches away the silicon oxide template and cerium oxide, and cerium fluoride has been successfully prepared.

[0060] The catalysts prepared in Example 1 and Comparative Example 1 were subjected to ECSA test, impedance test and stability test. The results are as follows: Figure 3 to Figure 5 As shown. Figure 3 The electrochemical activity area diagram of the catalyst shows that the porous cerium fluoride supported platinum catalyst has the highest electrochemical activity area. The larger the area, the more active sites the catalyst has, thus having a higher methanol catalytic performance. Figure 4 The impedance spectrum shows that the impedance arc of the porous cerium fluoride supported platinum catalyst is the smallest because the introduction of fluoride ions reduces the impedance arc, indicating that the charge transfer efficiency is improved and the conductivity of the catalyst is enhanced. Figure 5 The stable test spectrum shows that the current gradually decreases with the increase of time, and the current rate decreases faster in the initial stage. This is attributed to the fact that the intermediate toxic species produced in the electrochemical process poison the Pt active site of the catalyst, which is difficult to be released, resulting in a rapid decrease in the current. However, after 600s, the current decrease rate of the catalyst sample tends to be slow, and the current decrease rate of the porous cerium fluoride supported platinum catalyst is the smallest, indicating that the porous cerium fluoride supported platinum catalyst has the best stability.

[0061] Example 2

[0062] This embodiment provides a porous cerium fluoride catalyst, and the preparation method thereof comprises the following steps:

[0063] Weigh 80g of cerium nitrate, 40g of dicyandiamide, and 160g of silicon dioxide, dissolve in 4L of water, stir and mix at a stirring rate of 600rpm for 12h to form a yellow solution, heat and evaporate at 120℃ for 5h, and then calcine in a muffle furnace at 650℃ for 4h to obtain a composite oxide; 70g of the composite oxide is added to 10L 5mol / L hydrofluoric acid solution was etched at 30°C for 2h at a stirring rate of 400rpm, and then filtered, washed and dried to obtain porous cerium fluoride; 20g of porous cerium fluoride, 5L of 0.02mol / L chloroplatinic acid solution, 70g of graphene, and 10L of ethylene glycol solution were mixed, ultrasonicated at 20KHz for 30min, and then stirred at a stirring rate of 800rpm for 3h, and then placed in a reactor for hydrothermal reaction at 120°C for 2h to obtain a black turbid liquid, which was vacuum filtered at a pump pressure of 0.09MPa for 2h, and then vacuum dried at 60°C for 8h to obtain a porous cerium fluoride catalyst.

[0064] The electrochemical performance of the catalyst prepared in this example was tested. After adding the catalyst, the peak current density of electrocatalytic methanol could reach 1600 A / g. Pt .

[0065] Example 3

[0066] This embodiment provides a porous cerium fluoride catalyst, and the preparation method thereof comprises the following steps:

[0067] Weigh 100g of cerium nitrate, 100g of dicyandiamide, and 100g of silicon dioxide, dissolve them in 3L of water, stir and mix them at a stirring rate of 1100rpm for 24h to form a yellow solution, heat and evaporate at 120°C for 5h, and then calcine at 700°C in a muffle furnace for 6h to obtain a composite oxide; etch 100g of the composite oxide in 15L7mol / L hydrofluoric acid solution at a stirring rate of 400rpm at 30°C for 3h, then filter, wash, and dry to obtain Porous cerium fluoride; 50 g of porous cerium fluoride, 10 L of 0.1 mol / L chloroplatinic acid solution, 50 g of graphene, and 20 L of ethylene glycol solution were mixed, ultrasonicated at 30 kHz for 60 min, stirred at a stirring rate of 800 rpm for 3 h, then placed in a reactor and hydrothermally reacted at 140° C. for 2 h to obtain a black turbid liquid, vacuum filtered at a pump pressure of 0.09 MPa for 5 h, and then vacuum dried at 60° C. for 6 h to obtain a porous cerium fluoride catalyst.

[0068] The electrochemical performance of the catalyst prepared in this example was tested. After adding the catalyst, the peak current density of electrocatalytic methanol could reach 1700 A / g. Pt .

[0069] Example 4

[0070] This embodiment provides a porous cerium fluoride catalyst, and the preparation method thereof comprises the following steps:

[0071] Weigh 60g of cerium nitrate, 120g of dicyandiamide, and 180g of silicon dioxide, dissolve them in 1.2L of water, stir and mix them at a stirring rate of 1600rpm for 15h to form a yellow solution, heat and evaporate at 120°C for 5h, and then calcine at 750°C in a muffle furnace for 8h to obtain a composite oxide; 100g of the composite oxide is etched in 20L6mol / L hydrofluoric acid solution at a stirring rate of 400rpm at 30°C for 3h, and then filtered, washed, and dried to obtain a multi-layered composite oxide. Porous cerium fluoride; 80g of porous cerium fluoride, 30L of 0.08mol / L chloroplatinic acid solution, 60g of graphene, and 30L of ethylene glycol solution were mixed, ultrasonicated at 50KHz for 100min, stirred at a stirring rate of 800rpm for 3h, then put into a reactor for hydrothermal reaction at 150℃ for 4h to obtain a black turbid liquid, vacuum filtered at a pump pressure of 0.09MPa for 4h, and then vacuum dried at 60℃ for 8h to obtain a porous cerium fluoride catalyst.

[0072] The electrochemical performance of the catalyst prepared in this example was tested. After adding the catalyst, the peak current density of electrocatalytic methanol could reach 1870 A / g. Pt .

[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous cerium fluoride catalyst, characterized in that: The following steps are involved: Mixing cerium salt, dicyandiamide, silicon dioxide and water, and then heating to evaporate the water to obtain a composite precursor; calcining the composite precursor to obtain a composite oxide; The composite oxide is etched in hydrofluoric acid to obtain porous cerium fluoride; The porous cerium fluoride, a carrier, a platinum source aqueous solution and an alcohol solution are mixed, and then a hydrothermal reaction is carried out to obtain a porous cerium fluoride catalyst.

2. The method for preparing a porous cerium fluoride catalyst according to claim 1, characterized in that: The mass ratio of the cerium salt, dicyandiamide and silicon dioxide is 1-10:1-5:1-10.

3. The method for preparing a porous cerium fluoride catalyst according to claim 2, characterized in that: The process of mixing the cerium salt, dicyandiamide, silicon dioxide and water also includes stirring; the stirring time is 12 to 72 hours; and the stirring speed is 300 to 1600 rpm.

4. The method for preparing a porous cerium fluoride catalyst according to claim 1 or 2, characterized in that: The calcination temperature is 360-750° C. and the calcination time is 4-12 hours.

5. The method for preparing a porous cerium fluoride catalyst according to claim 4, characterized in that: The concentration of the hydrofluoric acid is 1-10 mol / L; the etching temperature is 10-40° C.; and the etching time is 1-3 hours.

6. The method for preparing a porous cerium fluoride catalyst according to claim 3, characterized in that: The usage ratio of the porous cerium fluoride, the carrier, the platinum source aqueous solution and the alcohol solution is 1-100g: 10-100g: 1-30L: 1-100L.

7. The method for preparing a porous cerium fluoride catalyst according to claim 6, characterized in that: The concentration of the platinum source aqueous solution is 0.01-0.2 mol / L; the platinum source in the platinum source aqueous solution is one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, and platinum acetylacetonate.

8. The method for preparing a porous cerium fluoride catalyst according to claim 5 or 7, characterized in that: The temperature of the hydrothermal reaction is 120-150° C.; the time of the hydrothermal reaction is 1-4 hours.

9. A porous cerium fluoride catalyst prepared by the method for preparing a porous cerium fluoride catalyst according to any one of claims 1 to 8.

10. Use of the porous cerium fluoride catalyst according to claim 9 in a fuel cell.

Citation Information

Patent Citations

  • CO oxidation catalyst in presence of moisture and carbon dioxide and preparation method of CO oxidation catalyst

    CN107649167A

  • Method for producing core shell nanoparticles

    CN108735980A

  • Nitrogen-doped carbon-loaded Pt metal catalyst for ammonia electrocatalytic oxidation as well as preparation method and application of nitrogen-doped carbon-loaded Pt metal catalyst

    CN114709433A

  • Cerium fluoride single crystal and production method thereof

    JP2016222496A

Cited By

  • Oxygen reduction functional electrode material, preparation method and application thereof

    CN120398206A